The Role of Empathy in Enhancing Customer Satisfaction: A Case Study of Laundry Services in Makassar - Dipoatmodjo, Tenri Sayu Puspitaningsih (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2024)
This study examines the role of empathy in enhancing customer satisfaction in the laundry service industry in Makassar City. Empathy is vital for building positive relationships by allowing service providers to better understand customers' feelings and needs. Through surveys and data analysis of laundry service users, the research identifies a significant correlation between high levels of empathy from providers and increased customer satisfaction. Key factors influencing empathy include employee training, interpersonal skills development, and an organizational culture that promotes empathy. The findings highlight the importance of empathy in a competitive market, offering insights for service management to improve customer experiences and foster loyalty through enhanced empathetic engagement.